Effect of the flask contention method on the displacement of maxillary denture teeth - Wagner Araújo Negreiros; Rafael Leonardo Xediek Rafael Leonardo Xediek Consani; Marcelo Ferraz Mesquita; Simonides Consani; Thiago Assunção Valentino (Universidade Estadual de Campinas, 2016)
Keeping the flask closed may reduce the stress released by the resin dough after the pressing step, preserving the tooth relationship pattern. The aim of this study was to analyze the influence of the flask contention method on tooth displacement in acrylic resin complete dentures. Twenty identical maxillary complete dentures were made using the heat-cured acrylic resins Classico and QC-20, polymerized by long and fast polymerization cycles respectively, and randomly assigned to 4 test groups according to the conventional packing method and RS tension system. Transversal and anteroposterior distances between specific teeth were measured with a linear optical microscope before and after denture processing. Analysis of variance (ANOVA) and Tukey test were used to compare the groups (p<.05). Results showed that tooth movement was significantly greater for the distance RI-LI in comparison with the others, and the tooth movement was not significantly influenced by the packing method. Within the limitations of this study, the RS tension system presented a similar performance in reducing the tooth movement, when compared with the conventional packing method. The anterior region of the denture may present changes in the tooth position after processing, which need to be clinically adjusted.